Measuring occupational performance supporting best practice in occupational therapy - Law, Mary C.; Baum, Carolyn Manville; Dunn, Winnie (Thorofare, NJ SLACK Incorporated, 2017)
This book summarizes the measurement tools needed to assess client occupational performance, to provide the best intervention, and to document the effectiveness of that intervention. These measurement tools are not just a compilation of all that are available for measurement relevant to occupational therapy; they are an elite group of tools carefully selected by the editors through a process of rigorous theoretical, clinical, and scientific reasoning.
Measurement in occupational therapy Mary Law and Carolyn Baum -- Measurement concepts and practices Winnie Dunn -- Understanding measurement properties Susan Magasi, Apeksha Gohil, Mark Burghart, and Anna Wallisch -- Guiding therapist decisions for measuring outcomes in occupational therapy Mary Law and Joy MacDermid -- Identifying person factors that impact occupational performance assessment Monica S. Perlmutter and Meredith P. Gronski -- Using naturalistic measurement methods to understand occupational performance Mary A. Corcoran, Carolyn Baum, and Winnie Dunn -- Measuring occupational performance using a client-centered perspective Mary Ann McColl, and Nancy Pollock -- Self-management and self-determination Joy Hammel and Danbi Lee -- General measures of participation across the lifespan Mary Law, Winnie Dunn, and Carolyn Baum -- Overview of play and leisure Jenny Ziviani, PhD, Anne A. Poulsen, and Laura Miller -- Measuring work performance Vicki Kaskutas -- Measuring participation at school Winnie Dunn, Becky Nicholson, and Lauren Foster -- Measuring occupational performance in basic activities of daily living Lori Letts and Jackie Bosch -- Measuring performance in instrumental activities of daily living Margo B. Holm and Joan C. Rogers -- Measuring time use and occupational balance Catherine Backman and Mary Forhan -- Measuring environmental factors Patricia Rigby, Oana Craciunoiu, Jill Stier, and Lori Letts -- Measuring social factors Julie D. Bass and Kathryn M.B. Haugen -- Applying an occupational performance measurement approach: challenges and strategies in implementation Mary Law, Carolyn Baum, and Winnie Dunn.
Includes bibliographical references and index.
Keywords: Occupational therapy; Outcome assessment (Medical care); Occupational therapy -- Decision making; Occupational Therapy -- standards; Outcome Assessment (Health Care); Guides de bonnes pratiques cliniques comme sujet; Practice Guidelines as Topic; Evidence-Based Medicine